Efektivitas dan Efisiensi Pembelajaran Bahasa Arab dengan Kitab Al Arabiyah Baina Yadaik di Kelas 1 Salafiyah Wustho Pondok Pesantren Islamic Centre Bin Baz - Muhammad Syafii Tampubolon (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2022)
In general, foreign language learning places great emphasis on the results achieved, especially learning Arabic. Regarding the achievement obtained from an effective and efficient learning process, it depends on whether the subject matter is systemized properly or not. Therefore, the learning process must be properly linked between the materials, media and methods used in learning the Arabic language. Kitab Al Arabiyah Baina yadaik is divided into two types, the first is a study guide book for students and the second is a guide book for teachers. Arabic learning with the Al Arabiyah Baina yadaika book which is applied at the Islamic Center Bin Baz Islamic Boarding School class 1 Salafiyah wustho starting from the 2021 school year, globally, students who take Arabic in first grade Salafiyah wushto do not yet have sufficient Arabic language base, will but after one year the students followed the Arabic language using the Al Arabiyah Baina book, there was a pretty good improvement.